Jaringan Kerjasama Perpustakaan Sekolah Dalam Upaya Menjaga Eksistensi Perpustakaan - Rahima Husna; Eva Soraya; Ikbal Fauzi; Yusniah Yusniah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
The school library collaboration network is very important considering that the school library is seen as a library that lacks attention, both in terms of collection, arrangement, space, or even the librarian. Given the constraints of the library in general regarding its collection, within the scope of the school, the library is only known as a place to store student textbooks. Then the arrangement is not in accordance with the standard national classification rules, where in the school library the collection is arranged based on color or size. Then a room far from a place that should be able to preserve collections. Then the librarians, most of whom are school librarians are picket teachers, or Indonesian language teachers, or teachers who are about to retire, not librarians who are professions capable of managing libraries properly. So that all aspects in the library are arranged based on the teacher's thoughts, not based on standards that have been set as a quality library. By establishing cooperation between school libraries, it will maintain or even increase the existence of libraries in the public eye. Existence is very important to maintain the good name of the library in the public eye. Keywords: Cooperation Network, School Libraries, Library Existence